3x^2+23x-9=0

1 answer

To solve the quadratic equation 3x^2 + 23x - 9 = 0, we can use the quadratic formula:

x = (-b ± √(b^2 - 4ac)) / 2a

In this equation, a = 3, b = 23, and c = -9.

Plugging these values into the formula:

x = (-23 ± √(23^2 - 4*3*(-9))) / 2*3
x = (-23 ± √(529 + 108)) / 6
x = (-23 ± √637) / 6

Now we can simplify the expression under the square root:

√637 is approximately 25.24

Now we have two possible solutions for x:

x = (-23 + 25.24) / 6
x = 2.24 / 6
x = 0.3733

and

x = (-23 - 25.24) / 6
x = -48.24 / 6
x = -8.04

Therefore, the solutions to the quadratic equation 3x^2 + 23x - 9 = 0 are x = 0.3733 and x = -8.04.